Efek Suplementasi Vitamin A, Minyak Fortifikasi dan Edukasi Gizi Ibu Nifas terhadap Morbiditas Ibu dan Bayi - Abdul Salam; Dodik Briawan; Drajat Martianto; Abdul Razak Thaha; Andi Imam Arundhana (Media Kesehatan Masyarakat Indonesia, 2018)
Vitamin A deficiency can affect the morbidity of postpartum mother and their infant. The purpose of thisstudy was to determine the effect of high doses of vitamin A (2vitA and 1vitA), fortified oil (Forti A) and nutritioneducation (Education) on maternal and infant morbidity. This study was used quasi experimental design with total295 samples selected based on the inclusion criteria. Morbidity which mainly associated with ARI and diarrheawas measured every two weeks until the infant is 3 months old. The results showed that the average postpartummothers in this study were 27 years old and about 42% of postpartum mothers had completed their education upto high school level. The average frequency of maternal ARI in the Forti A group was lower compared to the 2vitA,1vitA and educational groups (0.04, 0.31, 0.95, and 0.29, respectively) (p<0.000). Likewise, it is also found in theduration of respiratory infection for each group of; 0.17, 0.99, 3.16, and 1.07 day, respectively (p<0.000). Oilfortification with vitamin A can reduce the incidence of morbidity.